Partnering with school providers to codesign mental health interventions: An open trial of Act & Adapt in urban public middle schools. Issue 11 (19th June 2020) - Bearman, Sarah K.; Bailin, Abby; Rodriguez, Erin; Bellevue, Alison
Abstract: Schools are well positioned to provide access to youth mental health services, but implementing effective programs that promote emotional and behavioral functioning in school settings is complicated by the poor fit of interventions developed in research settings to complex school contexts. The current study formed a research–practice partnership with two urban public schools and mental health providers employed by those schools ( N = 6, 100% female, 50% Black/African American, 50% White/Caucasian) in the adaptation of a depression prevention intervention, Act & Adapt. The intervention was modified by decreasing meeting time and streamlining session content, increasing flexibility, making intervention materials more similar to academic curriculum, and increasing the focus on managing disruptive behavior within group sessions. In an open trial, sixth‐grade students ( N = 22; 59% boys, 31% Hispanic, 22% Black/African American, 4% Asian, 30% White/Caucasian) at both schools who were identified as clinically "at risk" reported improvements from baseline to postintervention and at 1‐year follow‐up on measures of emotional and behavioral difficulties and coping strategies, with parallel results by caregiver report. The providers reported satisfaction with the intervention, and qualitative analyses of provider focus groups suggested both barriers and facilitators to research‐practice collaborations to implement mental health interventions in schools.